Critical Appraisal of Emergency Medicine Educational Research: The Best Publications of 2016. Issue 1 (14th December 2018) - Dubosh, Nicole M.; Jordan, Jaime; Yarris, Lalena M.; Ullman, Edward; Kornegay, Joshua; Runde, Daniel; Juve, Amy Miller; Fisher, Jonathan
Abstract: Objectives: The objectives were to critically appraise the emergency medicine (EM) medical education literature published in 2016 and review the highest‐quality quantitative and qualitative studies. Methods: A search of the English language literature in 2016 querying MEDLINE, Scopus, Education Resources Information Center (ERIC), and PsychInfo identified 510 papers related to medical education in EM. Two reviewers independently screened all of the publications using previously established exclusion criteria. The 25 top‐scoring quantitative studies based on methodology and all six qualitative studies were scored by all reviewers using selected scoring criteria that have been adapted from previous installments. The top‐scoring articles were highlighted and trends in medical education research were described. Results: Seventy‐five manuscripts met inclusion criteria and were scored. Eleven quantitative and one qualitative papers were the highest scoring and are summarized in this article. Conclusion: This annual critical appraisal series highlights the best EM education research articles published in 2016.